XXVIII Open Seminar on Acoustics Gliwice, 7–11 September, 1981 - RYFFERT, H. (Archives of Acoustics, 1982)
XXVIII Open Seminar on Acoustics (OSA 81) was held in Gliwice on 7·11 September. 1981. It was organized by the High Silesian Division of the Polish Acoustical Society and the Institute of Physics, Silesian Technical University.